The Influence of the Cooperative Learning Model on Students' Absorption in Islamic Education Subjects at SMP Negeri 1 Panga - Erlina (MANDAILING GLOBAL EDUKASIA, 2024)
The Influence of Cooperative Learning Model on Students' Absorption in Islamic Religious Education Subjects at SMP Negeri 1 Panga, Aceh Jaya Regency